2007
DOI: 10.2135/cropsci2006.12.0821
|View full text |Cite
|
Sign up to set email alerts
|

Protein Changes during Heat Stress in Three Kentucky Bluegrass Cultivars Differing in Heat Tolerance

Abstract: Supraoptimal temperature limits growth and metabolic activities of cool‐season turfgrasses. Understanding genetic variations and mechanisms in turfgrass heat tolerance would facilitate breeding and management programs to improve turf quality under summer stress. The objective of this study was to investigate protein changes associated with heat tolerance in three Kentucky bluegrass (Poa pratensis L.) cultivars. Plants of ‘Brilliant’, ‘Midnight’, and ‘Eagleton’ were subjected to 20°C (day/night, control) or 40°… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
23
0
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 48 publications
3
23
0
1
Order By: Relevance
“…Our observations regarding increase in APX match with the findings in heat-stressed plants of mulberry (Chaitanya et al 2002) and wheat (Sairam et al 2000) while the inhibition in its activity at higher temperature is in agreement with the observations on Arabidopsis (Panchuk Irina et al 2002). Previously, it has been reported that the heat-tolerant genotype of Kentucky grass (Poa pratensis) had significantly higher APX activity than its sensitive genotype (He and Huang 2007). In our studies, the maize genotypes possessed appreciably higher APX activity at both these temperature regimes suggesting their higher capacity to neutralize hydrogen peroxide and also corroborating their tolerance to heat stress.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Our observations regarding increase in APX match with the findings in heat-stressed plants of mulberry (Chaitanya et al 2002) and wheat (Sairam et al 2000) while the inhibition in its activity at higher temperature is in agreement with the observations on Arabidopsis (Panchuk Irina et al 2002). Previously, it has been reported that the heat-tolerant genotype of Kentucky grass (Poa pratensis) had significantly higher APX activity than its sensitive genotype (He and Huang 2007). In our studies, the maize genotypes possessed appreciably higher APX activity at both these temperature regimes suggesting their higher capacity to neutralize hydrogen peroxide and also corroborating their tolerance to heat stress.…”
Section: Discussionsupporting
confidence: 84%
“…The heat-tolerant genotypes of wheat possessed higher expression of catalase (Balla et al 2009) compared to the sensitive ones. On the other hand, He and Huang (2007) observed greater CAT activity in heat-sensitive genotype of Kentucky grass (Poa pratensis). Our studies indicated that maize having higher CAT activity possessed better ability to remove hydrogen peroxide than rice genotypes.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Soluble protein content is an important indicator of changes in metabolism, and it is known to respond to a wide variety of stresses (Singh and Tewari 2003). A higher content of soluble protein has been reported in several plant species under adverse growth conditions (Ashraf and Harris 2004;He and Huang 2007).…”
Section: Influence Of Medium Ph On Biochemical Statusmentioning
confidence: 98%
“…Plant organic materials primarily comprise the constituents of the cell walls and cytoplasm. These include structural carbohydrates, such as cellulose, hemicellulose, and lignin; nonstructural carbohydrates, such as sucrose, fructose, and starch; proteins and other nitrogenous compounds, such as enzymes and nucleic acids; lipids, including waxes, pectins, and pigments; and secondary metabolites, such as terpenoids, alkaloids, and phenylpropanoids (Shearman and Beard, 1975;Hull, 1992;Paul and Clark, 1996;Horwath, 2002Horwath, , 2007Narra et al, 2004Narra et al, , 2005Brosnan et al, 2005;Watkins et al, 2006;He and Huang, 2007;Turgeon, 2008). These vary in proportion depending on the plant type and part, the age of the material, and the extent of decay (Shearman and Beard, 1975;Martens, 2000;Trenholm et al, 2000;Johnson et al, 2007).…”
mentioning
confidence: 99%